Типы соотношений фенотипических классов при агамоспермии - Кирикович, С.С.; Левитес, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. With the appearance of evidence of the existence of combinatorial processes due to differential polyteny of chromosomes and diminution of redundant chromatid segments, it became possible to understand and classify the nature of agamospermy for a much larger number of progenies. In this connection, this work aims to give an interpretation of the previously obtained and new experimental data. Methods. The ratios of enzyme phenotypic classes for alcohol dehydrogenase (ADH1), malic enzyme (ME1), isocitrate dehydrogenase (IDH3) were analyzed using electrophoresis in starch gel with further isozymes histochemical staining in electrophoregrams. Results. Phenotypic ratio types of agamospermous progenies obtained from 15 maternal plants were analyzed. It was shown that with the help of phenotypic classes ratios in the progenies it is possible to classify the type of agamospermy. Conclusions. This article focuses on the development of the method for the genetic classification of agamospermous reproduction types in plants using sugar beet as an example. The classification feasibility is ensured by the use of isozymes as genetic markers allowing the identification of all three phenotypic classes in the progeny of individual heterozygous diploid plant and is based on different phenotypic class ratios in the progenies obtained by meiotic and mitotic agamospermy.